SAS wave experiment on board Magion 4 - J. Błęcki; S. Gadomski; J. Juchniewicz; V. Korepanov; Z. Krawczyk; S. Savin; J. Słomiński; P. Triska; J. Vojta; R. Wronowski (Annales Geophysicae, 1997)
A short description of the SAS (subsatellite analyser of spectra) wave experiment on board the Magion-4 subsatellite is given. We present first measurements of the magnetic-field fluctuations in the frequency range 32–2000 Hz obtained in the magnetotail during the disturbed period at the magnetopause and in the polar cusp.